Effect of Mixed Cropping Between Zea maize and Arachis pintoi on the Nutrient Content of Grain and Straw - A. N. I. Insani; M Mariam; M. Yusuf; S. Sudarsono (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2026)
ABSTRACT This study aimed to evaluate the effect of mixed cropping of maize (Zea mays) with pinto peanut (Arachis pintoi) on the nutrient content of maize grain and straw. A randomized group design (RGD) was employed with five treatments and three replications. The treatments consisted of P0 (100% maize), P1 (80% maize + 20% legume), P2 (50% maize + 50% legume), P3 (20% maize + 80% legume), and P4 (100% legume). The parameters observed included crude protein, neutral detergent fiber (NDF), and acid detergent fiber (ADF) content of maize grain and straw. Analysis of variance revealed that mixed cropping had no significant effect (P>0.05) on the nutritional composition of both maize grain and straw. In conclusion, intercropping maize with Arachis pintoi does not significantly influence the nutritional quality of maize under the conditions of this study. Keywords: Arachis pintoi, maize feed, mixed cropping, production